"Measuring up" to ethical standards in service delivery to college students on the Autism Spectrum: A practical application of Powell's model for ethical practices in clinical phonetics and linguistics. (July 2014) - Weiss, Amy L.; Rohland, Pamela
Abstract This paper examined an interdisciplinary college-based support programme, the Communication Coaching Program (CCP), designed for students diagnosed on the autism spectrum in light of six ethical constructs described by Powell. Collecting data to monitor the successes and ongoing needs of individual participants in the programme is of vital importance, of course, but only addresses a portion of the efficacy question. In addition, the authors, who co-direct the programme and represent different professional expertise and perspectives, recognize the importance of determining whether their evolving intervention model has also been successful in meeting the ethical standards of their respective professions. Careful review of the 4 years of the CCP's operation in terms of ethical constructs has yielded evidence that the CCP, although based on sound principles of theory and scholarship, should be further individualized to meet the particular needs of participants diagnosed with deficits in social communication and executive functioning skills.